Barriers to Using Economic Experiments in Evidence‐Based Agricultural Policymaking. Issue 2 (5th October 2020) - Rosch, Stephanie; Raszap Skorbiansky, Sharon; Weigel, Collin; Messer, Kent D.; Hellerstein, Daniel
Abstract: Economic experiments have been used to inform evidence‐based policymaking in a variety of fields but have rarely been used to address agricultural policy topics in the United States. Several barriers exist in designing and funding experimental studies with farmer participants, which limits the usefulness of this approach for informing agricultural policymaking. We review three such barriers: heterogenous treatment effects, access to participants, and aligning funding agencies' priorities. We document the extent of these barriers using original analyses of the literature. We then suggest potential methods of mitigating these barriers through changes in how experiments are designed, reviewed, and funded. Abstract : Related Content: Challenges in Recruiting U.S. Farmers for Policy-Relevant Economic Field Experiments